Bridging Cultural Contexts and Digital Innovation in Mathematics Learning: A Meta-Analytic of Augmented Reality Supported Ethnomathematics - Maximus Tamur; Muhammad Afrilianto; Potchong M. Jackaria; Nilo Jayoma Castulo; Ayubu Ismail Ngao (Universitas Muhammadiyah Mataram, 2026)
The integration of cultural perspectives into Mathematics Education has expanded significantly alongside the rapid development of Augmented Reality (AR). While prior reviews have separately examined digital innovation in mathematics learning or the role of ethnomathematics in culturally responsive pedagogy, no previous meta-analysis has systematically synthesized empirical evidence at the intersection of augmented reality and ethnomathematics. This study addresses that gap by providing the first quantitative synthesis of the effectiveness of AR-supported ethnomathematics across educational levels, thereby bridging cultural context and digital innovation within a single analytical framework. Using a meta-analytic approach, quantitative findings from 21 empirical studies (selected from an initial pool of 101 studies indexed in Google Scholar and Scopus) were synthesized using a random-effects model in Comprehensive Meta-Analysis (CMA). The overall effect size was large and positive (ES = 1.10), demonstrating that AR-supported ethnomathematics substantially improves students’ mathematics learning outcomes compared to conventional approaches. Moderator analyses revealed significant heterogeneity, with stronger effects observed in interventions that integrated interactive and contextually immersive AR features and at the primary and secondary education levels. The magnitude of the effect (ES = 1.10) indicates not merely statistical significance but strong practical relevance, suggesting that integrating culturally grounded mathematical contexts with immersive AR technology can meaningfully enhance conceptual understanding, engagement, and knowledge retention. For curriculum development, these findings support the systematic incorporation of AR-based ethnomathematical modules into mathematics syllabi, particularly in culturally diverse settings. Rather than positioning digital innovation as a supplementary tool, the results advocate for its structural integration into culturally responsive curriculum design. Future research should employ longitudinal and mixed-method designs to examine the sustainability of these effects and to explore how evolving digital innovations influence students’ cognitive and affective learning trajectories over time.